β-catenin nuclear translocation induced by HIF-1α overexpression leads to the radioresistance of prostate cancer - Luo, YONG; Li, MINGCHUAN; Zuo, XUEMEI; BASOURAKOS, SPYRIDON P.; Zhang, JIAO; Zhao, JIAHUI; Han, Yili; Lin, YUNHUA; Wang, YONGXING; Jiang, YONGGUANG; Lan, Ling (My University, 2018)
Hypoxia-inducible factor-1α (HIF-1α) is known to play crucial roles in tumor radioresistance; however, the molecular mechanisms responsible for the promotion of tumor radioresistance by HIF-1α remain unclear. β-catenin is known to be involved in the metastatic potential of prostate cancer (PCa). In this study, to investigate the role of HIF-1α and β-catenin in the radioresistance of PCa, two PCa cell lines, LNCaP and C4-2B, were grouped as follows: Negative control (no treatment), HIF-1α overexpression group (transfected with HIF-1α overexpression plasmid) and β-catenin silenced group (transfected with HIF-1α plasmids and β-catenin-shRNA). Cell proliferation, cell cycle, cell invasion and radiosensitivity were examined under normal or hypoxic conditions. In addition, radiosensitivity was examined in two mouse PCa models (the LNCaP orthotopic BALB/c-nu mice model and the C4-2B subcutaneous SCID mice model). Our results revealed that in both the LNCaP and C4-2B cells, transfection with HIF-1α overexpression plasmid led to an enhanced β-catenin nuclear translocation, while β-catenin silencing inhibited β-catenin nuclear translocation. The enhanced β-catenin nuclear translocation induced by HIF-1α overexpression resulted in an enhanced cell proliferation and cell invasion, an altered cell cycle distribution, decreased apoptosis, and improved non-homologous end joining (NHEJ) repair under normal and irradiation conditions. Similar results were observed in the animal models. HIF-1α overexpression enhanced β-catenin nuclear translocation, which led to the activation of the β-catenin/NHEJ signaling pathway and increased cell proliferation, cell invasion and DNA repair. These results thus suggest that HIF-1α overexpression promotes the radioresistance of PCa cells.